ELEKTISITAS PEMASARAN KAIN TENUN SONGKET MELAYU RIAU PADA DEKRANASDA PROVINSI RIAU - Yuzalmi, Nanik (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
The Regional Handicraft Board (Dekranasda) of Riau Province, in line with its vision andmission, seeks to preserve and grow craft, for the sake of sustainability and continuity as wellas continuity of handicraft production departing from the traditional artistic cultural values ofsociety with songket fabric of Riau Malay. But the realization of marketing from year to yearhas not met the target and even decreased, this is the main concern Tenran Dekranasda incarrying out its marketing efforts. The method used in this research is descriptive method byusing qualitative analysis and data analysis by linking between theory and problem studied.The problem in this research is the factors of woven fabric songket Malay Riau. The results ofthe research are: - Firstly, the marketing target of songket fabric of Riau Malay is caused by:product, price, promotion and distribution. Second, product marketing, in this case is aproduct of Malay songket woven fabric offered to the target market. Third, the interest ofconsumers or buyers on the woven fabric of Riau Malay songket product is caused by thequality factor, the motive and the color with the activity that communicates with the value ofthe product and conveys the persuasion to the consumers on the products offered. Fourth,Promotion given in the form of promotion to advertisement and sales promotion. Fifth, thedistribution of woven cloth of Riau Malay songket which is distributed directly or indirectlyand according to the buyer's buyer rating is considered good.Keywords: Product, Price, Promotion and Distribution